2019
DOI: 10.3389/fmicb.2019.00351
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Phases and Cell Geometry During the Cell Cycle of Streptococcus pneumoniae

Abstract: The coexistence of different lipid phases is well-known in vitro, but evidence for their presence and function in cellular membranes remains scarce. Using a combination of fluorescent lipid probes, we observe segregation of domains that suggests the coexistence of liquid and gel phases in the membrane of Streptococcus pneumoniae, where they are localized to minimize bending stress in the ellipsoid geometry defined by the cell wall. Gel phase lipids with high bending rigidity would be spontaneously organized at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…To compensate, membrane fluidity and peptidoglycan synthesis activity is increased at division sites in flotillin mutants, which is sufficient to keep the overall cell shape intact, although cells are elongated. The increased fluidity at division sites is in line with a recent study that showed phases of different fluidity in Streptococcus pneumoniae membranes, with more fluid membranes and LipidII localizing at midcell 42 where the membrane is most bent. It may seem paradoxical that cells elongate when elongasome activity is reduced, but one has to remember that a large amount of the peptidoglycan synthesis contributing to elongation of bacterial cells is actually taking place at midcell, before the ingrowth of the septum 43-45 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…To compensate, membrane fluidity and peptidoglycan synthesis activity is increased at division sites in flotillin mutants, which is sufficient to keep the overall cell shape intact, although cells are elongated. The increased fluidity at division sites is in line with a recent study that showed phases of different fluidity in Streptococcus pneumoniae membranes, with more fluid membranes and LipidII localizing at midcell 42 where the membrane is most bent. It may seem paradoxical that cells elongate when elongasome activity is reduced, but one has to remember that a large amount of the peptidoglycan synthesis contributing to elongation of bacterial cells is actually taking place at midcell, before the ingrowth of the septum 43-45 .…”
Section: Discussionsupporting
confidence: 89%
“…Our data indicate that the reduction in elongasome activity, which does not impact the growth rate itself, is compensated by increased peptidoglycan synthesis activity around division sites in flotillin mutants, which is sufficient to keep the overall cell shape intact, although cells are elongated. The accumulation of lipid dyes indicative of increased fluidity at division sites is in line with a recent study that showed phases of different fluidity in Streptococcus pneumoniae membranes, with more fluid membranes and LipidII localizing at midcell 47 where the membrane is most bent. Our findings are also in agreement with the recent observation that B. subtilis cells elongate and lose organization of MreB when membrane fluidity is decreased by altering the membrane fatty acid composition 48 (H. Strahl, personal communication).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, the speed of MreB patches is also sensitive to the fluidity of the cytoplasmic membrane, which is controlled by the two flotillins FloA and FloT, and membrane fluidity is linked to growth medium composition (Bach and Bramkamp, 2013;Zielińska et al, 2020). Thus, it may be membrane fluidity rather than growth rate which controls MreB movement, by creating a favourable environment for LipidII which prefers more fluid membrane patches (Calvez et al, 2019;Zielińska et al, 2020).…”
Section: Morales Angeles and Scheffersmentioning
confidence: 99%